Pemaknaan lagu day6 zombie (english version) terhadap fenomena quarter life crisis: Studi pada kalangan mahasiswa ilmu komunikasi - Pratiwi, Shafiyah Nanda; Harsono, Ari (Journal of Youth and Outdoor Activities, 2024)
The phenomenon of quarter life crisis is a phase when someone begins to feel unstable, doubtful, afraid, and indecisive to continue their life. Afterwards, this tendency developed into social issue that is prevalent among young generation these days. Preventive action to reduce the negative impact of the quarter life crisis is to utilize a coping mechanism as a self-defense strategy. A song with a specific message can help the process of dealing with or overcoming such a crisis. One of them is Day6's song Zombie (English Version). This study analyzes reception of the Day6’s song Zombie (English Version) among Communication Science students of University of Indonesia towards the quarter life crisis phenomenon. The study was carried out using qualitative methods and an interpretive paradigm. This study concludes that each informant is in various positions when interpreting the message content in the Zombie (English Version). Informants who are going through a quarter-life crisis tend to understand Zombie songs more profoundly and explicitly, connecting song lyrics with personal issues, instability, and lack of direction as well as querying the existence of life. A Zombie song can serve as a catharsis for coping strategies that help listeners convey their emotions and sentiments in a positive direction. Informants who haven't gone through a quarter-life crisis, however, will interpret the Zombie song more broadly, interpreting it as conveying grief, failure, and overall hesitation.